Kinetic study of carbothermal reduction of zirconia under vacuum condition - Kazemi, Faramarz; Arianpour, Farzin; Rezaie, Hamid Reza (Springer Science and Business Media LLC, 2019)
In this research, formation mechanism and kinetics of vacuum carbothermal synthesis of zirconium carbide using zirconium acetate and sucrose are discussed. The study of non-isothermal reduction was conducted by thermogravimetry analysis and heating the samples in argon and vacuum conditions up to 1773 K, and then the heat exchange values of reactions were calculated. Isothermal formation mechanism of carbide phase was investigated by heating the samples at 1473 K and 1673 K in argon and vacuum atmospheres followed by X-ray diffraction and quantitative phase analysis. Results showed that in non-isothermal state, the carbothermal reduction of zirconia is a heterogeneous reaction with multiple steps. For isothermal reaction, the kinetic parameters such as activation energy and pre-exponential factor were calculated as 70.56 kJ mol−1 and 11.22 × 10−2 S−1, respectively. It was presented that the activation energy value extracted from isothermal reaction is completely in accordance with the final step of non-isothermal results.
Keywords: 7. Clean energy